Daily health concerns in Kakabo : anthropological explorations in a Bangladeshi village - Geest, Sjaak van der, 1943-; Selim, Nasima; Zaman, Shahaduz, 1962- (Monograph series ;, 2008)
Study of Kakabo village near Dhaka, Bangladesh.